Influencia del Tamaño de la Empresa y la Rama de Actividad en la Afiliación a la Seguridad Social de los Trabajadores del Sector Privado Ecuatoriano en el 2021 - Aguirre Cabrera, Jaime Daniel (2023)
On 2020, the Ecuadorian Institute of Social Security (IESS) had 2,672,400 contributors to the mandatory general insurance (SGO), while the economically active population (EAP) in that year was 8,090,249; in other the other hands, the majority of Ecuadorian workers were not affiliated with the SGO. For this reason, this research work aims to analyze the influence of the company size and industry branch on the affiliation to social security of private sector workers in Ecuador in 2021, using descriptive statistics and econometric models, in order to propose public policies aimed at maximizing affiliation to the Social Security System in Ecuador. To achieve this, data from the National Survey of Employment, Underemployment, and Unemployment (ENEMDU) were used to perform descriptive statistics and discrete choice models. The main results showed that the company size has a significant influence on the affiliation to workers ́ social security, as well as the industry branch, although to a lesser extent. In contrast, the other variables: area, age, education, income salary, and ethnicity, have a smaller impact on affiliation to Social Security. Consequently, preventive and corrective measures are recommended, such as incentives and random inspections, to increase the percentage of affiliation to the Ecuadorian SGO.